Restless Subjects in Rigid Systems : Risk and Speculation in Millennial Fictions of the North American Pacific Rim. - Wegener, Susanne (transcript Verlag, 2014)
The anticipatory logic of speculation and preemptive politics of risk are increasingly gaining significance in a globalizing neoliberal world. This study traces risk and speculation as aesthetic and political-economic strategies in factual and fictional discourses emerging at the North American Pacific Rim within a decade around 2000. Its exemplary close readings in particular focus on three fictional texts (Kathryn Bigelow's Hollywood film »Strange Days±, 1995, Karen T. Yamashita's novel »Tropic of Orange±, 1997, and Larissa Lai's novel »Salt Fish Girl±, 2002) whose intricate aesthetics pass.
Introduction : dealing in futures -- Are you paranoid enough? Kathryn Bigelow's Strange Days and the politics of risk and speculation -- Live on the edge I say : edgework, risk, and literary form in Karen Tei Yamashita's Tropic of Orange -- Monstrous politics : epistemological empowerment, natural science, and new territories of empire in Larissa Lai's Salt Fish Girl -- Towards a poetics of risk and speculation.
Print version record.
In English.
eBooks on EBSCOhost
Keywords: American literature -- History and criticism; American fiction -- Themes, motives; Risk in literature; Speculation -- In literature; Roman américain -- Thèmes, motifs; Risque dans la littérature.; Spéculation -- Dans la littérature.; LITERARY CRITICISM -- American -- General; LITERARY CRITICISM / American / General; American fiction -- Themes, motives; American literature; Risk in literature; Criticism, interpretation, etc